Leviathans at the Gold Mine : Creating Indigenous and Corporate Actors in Papua New Guinea - Golub, Alex (Book collections on Project MUSE., 2014)
Leviathans at the Gold Mine is an ethnographic account of the relationship between the Ipili, an indigenous group in Papua New Guinea, and the large international gold mine operating on their land. It was not until 1939 that Australian territorial patrols reached the Ipili. By 1990, the third largest gold mine on the planet was operating in their valley. Alex Golub examines how ""the mine"" and ""the Ipili"" were brought into being in relation to one another, and how certain individuals were authorized to speak for the mine and others to speak for the Ipili. Considering the relativ.